An Investigation of Femtocell Network Synchronization - Hasan, Mohammad Kamrul; Saeed, Rashid Abdelhaleem; Hassan Abdalla Hashim, Aisha; Islam, Shayla; Mahmoud, Omer; Khalifa, Othman Omran; Hameed, Shihab A.; Ismail, Ahmad Fadzil (2011)
Currently, Femtocell technology emerged for cellular wireless networks, which has rapidly engrossed cellular industry. The principle of femtocell to the mobile operators is to reduce cost and improve signal quality in indoor coverage which is also considered a possible path to the fixed–mobile convergence (FMC) goal. Femtocell extends network coverage and delivers high-quality mobile services inside residential and business buildings through broadband network i.e. ADSL. Femtocell access point (FAP) or home base station (HBS) intends to serve small number of users i.e. 4 users and covers about 30 meter square similar to existing WiFi access points. However, femtocell introduces new challenges to the telecom industries in terms of handoff between femto and macrocells, interference management, localization and synchronization. Among all of these challenges, synchronization is considered corner stone for proper working for femtocell. The problematic issue in femtocell synchronization is that all the data and control traffics travel through IP broadband network. The IP broadband network is usually owned and managed by third party and not by the mobile operator, which is complicated the synchronization. Unsynchronized FAPs may cause harm interferences and wrong handover dictions. In this study we investigate and overview the current femtocell synchronization techniques and compare between them. Possible improvements and recommendation for each method is identified. Proposed schemes and indicated future research areas are also discussed.